Yield state investigation of reinforced concrete frames from a new point of view - Yüksel, I; Polat, Z (ELSEVIER SCI LTD, 2005)
The global yield state of building frame systems is underestimated by the conventional approach. A new criterion is proposed in this paper for defining the system yield point of reinforced concrete frameworks from a new point of view. The criterion is named 'First Significant Member Yield (FSMY)' and is used to estimate the global system yield displacement. To estimate the yield parameters of reinforced concrete frame systems, a capacity curve is drawn with respect to period versus base shear force instead of base shear versus top displacement. As the base shear force remains approximately constant, the fundamental period starts to lengthen considerably at a special point. At FSMY the system starts to yield as a whole. At this point, the lateral displacement, the fundamental period and the base shear force values can be accepted as system yield parameters. Numerical applications were conducted on two frames and two typical building structures by using pushover analysis as a tool. A dramatic increase in the first natural vibration period of the system makes it easier to identify the FSMY. Variation of the fundamental period of the structure with respect to base shear could be of benefit as an indicator for defining the system yield displacement. By using the proposed FSMY approach, the system yield displacement could be determined more sensitively than by, the conventional approach. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: capacity curve; displacement; ductility; first period; frame; yield; WALLS; Engineering